Biosynthesis Of Polyhydroxyalkanoate (Pha) Using Waste Fish Oil By Cupriavidus necator H16 - Puvaneswary , Kaesavan (2014)

(untitled)
The potential use of waste fish oil (WFO) as carbon source for production of polyhydroxyalkanoates (PHAs) using Cupriavidus necator H16 was investigated. Small aggregates of the WFO were observed to be floating on the surface of culture medium, which limited the accessibility of the carbon source to the bacterium. Potensi penggunaan sisa minyak ikan sebagai sumber karbon untuk penghasilan polihidroksialkanoat (PHA) oleh Cupriavidus necator H16 telah disiasat. Pengumpalan sisa minyak ikan kelihatan terbentuk dan terapung di permukaan media.